The Influence of Direct Marketing and Brand Ambassador on Repurchase Interest of Tiktok Users in Yogyakarta - Ismawati, Tri; Prasetyo, Heri (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research aims to analyze the influence of direct marketing and Brand Ambassador on the repurchase intentions of TikTok application users in Yogyakarta City. Using a quantitative and associative approach, data was collected through a questionnaire distributed to 100 TikTok users in Yogyakarta. The results of multiple linear regression analysis show that direct marketing and the Ambassador brand have a significant influence on repurchase intentions, both partially and simultaneously. Direct marketing, which involves direct communication between sellers and buyers, has been proven to be effective in increasing willingness to repurchase significantly. Apart from that, choosing the right brand ambassador who is attractive, trustworthy and has relevant skills also has a positive impact on consumers' desire to make repeat purchases. These findings highlight the importance of direct marketing and brand ambassadors in marketing strategies to increase consumer loyalty and repurchase intentions for products or services offered through the TikTok application.